Formulasi dan Uji Stabilitas Sediaan Suspensi Ekstrak Rimpang Zingiber zerumbet - Shafa Shavira; Angel Dineta Margaretta; Aprilia Dwi Sandra; Raya Uli Sitorus; Fatmaria Fatmaria (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2021)
Zingiber zerumbet (L) Smith rhizome has been used traditionally as an herbal medicine in Indonesia. Isolated extracts and metabolites of Z. zerumbet have shown anti-inflammatory, antioxidant, antidiabetic, anticancer, antimicrobial, analgesic and antiviral activity. The form of suspension is carried out to facilitate the utilization of the main bioactive content, zerumbone, which is difficult to dissolve in water. The formulation of suspension is based on variations in the concentration of Z. zerumbet extract, which is 2.5% (formulation 1), 5% (formulation 2), and 10% (formulation 3). To determine the physical stability, the evaluation is carried out, namely: organoleptic test, density, viscosity, redispersibility and pH. The results showed all three formulations did not provide organoleptic changes for 30 days, >1 g/cm3 density, good redispersibility, and pH of 6. The viscosity of each formulation is quite varied i.e., 3.74 cp; 4,27 cp; and 11.8 cp. Formulation 3 is determined as the best formulation based on its viscosity which is closest to the standard range of good suspension viscosity according to the SNI.